PAPUA PEOPLE ASSEMBLY CHOOSES NON-MUSLIM LEADERS IN NON-MUSLIM MAYORITY REGIONS IN MASHID SYARI'AH PERSPECTIVE IN JAYAPURA CITY IN PAPUA PROVINCE - Podu, Sobar; Gassing, A. Qadir; Jafar, Usman; Talli, Abd. Halim (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This paper elaborates on the Papuan People's Assembly Electing Non-Muslim Leaders in Non-Muslim Majority Areas in the Perspective of Mashid Syari'ah in Jayapura City, Papua Province. The results of this study indicate that the Papuan People's Council (MRP) elects leaders in non-Muslim majority areas in the perspective of maqasid syari'ah in Papua, in its role in the process of organizing the selection of prospective leaders in Papua, has taken away the rights of citizens in general. it is decided by the competent authority of the Papuan People's Assembly (MRP) following what has been decided by formal institutions, such as the General Election Commission (KPU) and traditional institutions that have been given authority according to law. In the provisions of Law No. 21 of 2001 on Papua Special Autonomy, there is no room or space for immigrants. As for the recruitment process for prospective leaders such as Governors and Deputy Governors based on Law No. 21 of 2001 The basic matters that constitute the contents of this Law include the arrangement of authority between the Government and the Provincial Government of Papua and the application of this authority in Papua Province which is carried out with specificity. This law places indigenous Papuans and the population of Papua in general as the main subjects. The existence of the Government, Provincial Government, Regency / City Government, as well as the apparatus under them, are all directed at providing the best service and empowering the people.